Clinical Characteristics and Outcome of Canadian Patients Diagnosed With Atypical Hemolytic Uremic Syndrome. (January 2020) - Lapeyraque, Anne-Laure; Bitzan, Martin; Al-Dakkak, Imad; Francis, Mira; Huang, Shih-Han S.; Kaprielian, Roger; Larratt, Loree; Pavenski, Katerina; Ribic, Christine; Tosikyan, Axel; Licht, Christoph; Philibert, David
Background: Atypical hemolytic uremic syndrome (aHUS) is an extremely rare, heterogeneous disease of uncontrolled activation of the alternative complement pathway that is difficult to diagnose. We have evaluated the Canadian patients enrolled in the Global aHUS Registry to provide a Canadian perspective regarding the diagnosis and management of aHUS and the specific challenges faced. Objective: To evaluate Canadian patients enrolled in the Global aHUS Registry to provide a Canadian perspective regarding the diagnosis and management of aHUS and the specific challenges faced. Methods: The Global aHUS Registry is an observational, noninterventional, multicenter study that has prospectively and retrospectively collected data from patients of all ages with an investigator-made clinical diagnosis of aHUS, irrespective of treatment. Patients of all ages with a clinical diagnosis of aHUS were eligible and invited for enrollment, and those with evidence of Shiga toxin–producing Escherichia coli infection, or with ADAMTS13 activity ≤10%, or a subsequent diagnosis of thrombotic thrombocytopenic purpura were excluded. Data were collected at enrollment and every 6 months thereafter and were analyzed descriptively for categorical and continuous variables. End-stage renal disease (ESRD)-free survival was evaluated using Kaplan-Meier estimates, and ESRD-associated risk factors of interest were assessed using Cox proportional hazards regression models. Patients were censored at start of eculizumab for any outcome measures. Results: A total of 37 Canadian patients were enrolled (15 pediatric and 22 adult patients) between February 2014 and May 2017; the median age at initial aHUS presentation was 25.9 (interquartile range = 6.7-51.7) years; 62.2% were female and 94.6% had no family history of aHUS. Over three-quarters of patients (78.4%) had no conclusive genetic or anti-complement factor H (CFH) antibody information available, and most patients (94%) had no reported precipitating factors prior to aHUS diagnosis. Nine patients (8 adults and 1 child) experienced ESRD prior to the study. After initial presentation, there appears to be a trend that children are less likely to experience ESRD than adults, with 5-year ESRD-free survival of 93 and 56% ( P = .05) in children and adults, respectively. Enrolling physicians reported renal manifestations in all patients at initial presentation, and 68.4% of patients during the chronic phase (study entry ≥6 months after initial presentation). Likewise, extrarenal manifestations also occurred in more patients during the initial presenting phase than the chronic phase, particularly for gastrointestinal (61.1% vs 15.8%) and central nervous system sites (38.9% vs 5.3%). Fewer children than adults experienced gastrointestinal manifestations (50.0% vs 70.0%), but more children than adults experienced pulmonary manifestations (37.5% vs 10.0%). Conclusions: This evaluation provides insight into the diagnosis and management of aHUS in Canadian patients and the challenges faced. More genetic or anti-CFH antibody testing is needed to improve the diagnosis of aHUS, and the management of children and adults needs to consider several factors such as the risk of progression to ESRD is based on age (more likely in adults), and that the location of extrarenal manifestations differs in children and adults.